Developmental and Immune Role of a Novel Multiple Cysteine Cluster TLR From Eisenia andrei Earthworms - Petra Prochazkova; Radka Roubalova; Frantisek Skanta; Jiri Dvorak; Natividad Isabel Navarro Pacheco; Miroslav Kolarik; Martin Bilej (Frontiers in Immunology, 2019)
Earthworms are not endowed with adaptive immunity and they are rely on the tools of innate immunity. Cells of the innate immune system utilize pattern recognition receptors, such as Toll-like receptors, to detect the pathogen-associated molecular patterns (PAMPs). The first earthworm TLR was isolated from Eisenia andrei earthworms (EaTLR), which belongs to the single cysteine cluster TLR (sccTLR). Here, we identified a new multiple cysteine cluster TLR (mccTLR) in E. andrei earthworms. Phylogenetic DNA analysis revealed that it has no variability within one earthworm as well as in the population. By screening of the tissue expression profile, the TLR was expressed primarily in earthworm seminal vesicles and receptacles suggesting a connection to sperm cells. Seminal vesicles are often heavily infected by gregarine parasites. As a sign of immune response, a strong melanization reaction is visible around parasites. Stimulation experiments with profilin from related parasite Toxoplasma gondii, led to the upregulation of mccEaTLR in the earthworm seminal vesicles. Also, profilin activated prophenoloxidase cascade, the efficient mechanism of innate immunity. However, its involvement in the NF-κB signaling was not proven. Further, we provide evidence that the antibiotics metronidazole and griseofulvin destroyed the developing spermatocytes. The observed decrease in the mccEaTLR mRNA levels after the antibiotic treatment of parasites is caused by the decline of sperm cells numbers rather than by diminution of the parasites. Since earthworms with extensively reduced parasite load had a similar amount of mccEaTLR mRNA, presumably, earthworm sperm cells have a certain level of mccEaTLR expressed as a standard, which can be augmented by particular antigenic stimulation. Also, mccEaTLR was expressed mainly in the early stages of earthworm development and presumably is primarily involved in early embryonic development. Expression of mccEaTLR in seminal vesicles correlates with the expression of endothelial monocyte-activation polypeptide II. High-throughput sequencing of gregarine DNA from seminal vesicles of individual earthworms resulted in great diversity of the observed genotypes. Phylogenetically, all observed OTUs belong to the clade of earthworm gregarines suggesting host specificity. Overall, mccEaTLR is supposed to play a function role in early embryonic development and potentially it participates in immune response against parasites.